Cultural Theory and History: The Change and Everyday Life - Bełkot, Andrzej; Kandulski, Stanisław; Kosińska, Marta (Wydawnictwo Naukowe Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The Change and Everyday Life is the next book of the series “Cultural Theory and History,” initiated during a seminary on this topic held in Institute of Cultural Studies at Adam Mickiewicz University. Here the authors follow different topics according to their own scholarly interest, ranging from the problems of everyday life to gender specifications within musical culture, united by common perspective of the explanation of diachronic sociocultural processes.
Keywords: cultural history; everyday life; cultural change; cultural studies; historiography